The Typical Spectral Shape of an Economic Variable - Granger, C. W. J. (Econometrica, 1966)
In recent years, a number of power spectra have been estimated from economic data and the majority have been found to be of a similar shape. A number of implications of this shape are discussed, particular attention being paid to the reality of business cycles, stability and control problems, and model building.